Denatured proteins facilitate the formation of the football-shaped GroEL-(GroES)2 complex - Sameshima, Tomoya; Iizuka, Ryo; Ueno, Taro; Funatsu, Takashi (Biochemical journal, 2010)
Controversy exists over whether the chaperonin GroEL forms a GroEL-(GroES)2 complex (football-shaped complex) during its reaction cycle. We have revealed previously the existence of the football-shaped complex in the chaperonin reaction cycle using a FRET (fluorescence resonance energy transfer) assay [Sameshima, Ueno, Iizuka, Ishii, Terada, Okabe and Funatsu (2008) J. Biol. Chem. 283, 23765-23773]. Although denatured proteins alter the ATPase activity of GroEL and the dynamics of the GroEL-GroES interaction, the effect of denatured proteins on the formation of the football-shaped complex has not been characterized. In the present study, a FRET assay was used to demonstrate that denatured proteins facilitate the formation of the football-shaped complex. The presence of denatured proteins was also found to increase the rate of association of GroES to the trans-ring of GroEL. Furthermore, denatured proteins decrease the inhibitory influence of ADP on ATP-induced association of GroES to the trans-ring of GroEL. From these findings we conclude that denatured proteins facilitate the dissociation of ADP from the trans-ring of GroEL and the concomitant association of ATP and the second GroES.